Incidence and type of restrictive practice use in residential disability facilities in Ireland, a cross‐sectional study. (29th September 2022) - Dunbar, Paul; Hazelwood, Emma; Wang, Qianru; McMahon, Martin; Walsh, Kieran A.; Keyes, Laura M.
Abstract: Restrictive practices (RPs) are a contentious issue in health and social care services. While use may be warranted in some instances, there are risks and concerns around human rights infringements. There are limited data available on the types and incidences of RPs used in health and social care services internationally. The objective of this study is to describe the type of RPs and incidence of use in disability residential care facilities (RCFs) in Ireland. RP notifications from disability RCFs reported from November 2019 to October 2020 were extracted from the Database of Statutory Notifications from Social Care in Ireland. National frequency and incidence of use of categories and type of RPs were calculated. The number and percentage of disability RCFs reporting RP use, along with the mean annual incidence of use, were also calculated. A total of 48, 877 uses of RPs were notified from 1387 disability RCFs (9487 beds) during the 12‐month period. The national incidence of RPs use per 1000 beds was as follows: all categories: 5152.0, environmental: 2988.2, physical: 1403.0, other: 527.0 and chemical: 233.8. The most frequently used RPs for each category was as follows: environmental: door locks, physical: other physical, other: liberty and autonomy and chemical: anxiolytics. Most RCFs (81.7%) reported at least one RPs use. The median incidence of any RPs per 1000 beds in these RCFs was 4.75 (IQR: 2.00 to 51.66). Usage of RPs was generally low, although some RCFs reported relatively high usage. Nationally, on average, five RPs were applied per resident over 12 months; environmental contributing to more than half. These findings can be used to inform policy, measure progress in reducing RPs use and for cross‐jurisdiction comparisons.